Development of Location Based Service Utilization System to Prevent Repeat Sexual Crimes - Hae Yoon, Ji; Kyoung Kang, Sun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently the number of victims of sexual offenses has increased from not only adults to but also to the elderly and children, greatly increasing the rate of repeat sexual offenses.Methods/Statistical Analysis: The system of this thesis has been developed based on the electronic ankle monitor system of existing sexual offenders and utilizing the location based system (LBS) of the user to prevent repeat sexual offenses. The system was developed using the GPS API built in smartphones for the location based service and using a virtual electronic ankle monitor to receive the latitude and longitude coordinates of the GPS to calculate the distance and azimuth between the smartphone and the virtual electronic ankle monitor. It is a real-time service that sends an alarm to the user of the risk of sexual crime when the distance between the smartphone and the virtual electronic ankle monitors enters a prescribed distance.Findings: The system developed in this paper compares the GPS values of the virtual electronic ankle monitor and the smartphone terminal. In order to confirm that the smartphone alarm went- off for risk of sexual crime when the distance between the two GPS values are within 1km, the virtual electronic ankle monitor was set to a latitude of 35.966927 and longitude of 126.954814 and the userâ€™s smartphone GPS was mobile and then experimented eight times. When the distance between the virtual electronic ankle monitor and the smartphone was measured within 1km for four times, the alarm for risk of sexual crime displayed â€œTrueâ€. When the test was measured four times with the distance between the virtual electronic ankle monitor and the smartphone exceeding 1km, the alarm for risk of sexual crime displayed â€œFalseâ€.Improvement/Applications: The system proposed in this paper is expected to reduce the incidence of sexual crimes by using the values of the electronic ankle monitor GPS and the userâ€™s smartphone GPS.Â